2020
DOI: 10.1038/s41416-020-0994-4
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural immunotherapies for unresectable and metastatic melanoma: current status and future perspectives

Abstract: The emergence of human intratumoural immunotherapy (HIT-IT) is a major step forward in the management of unresectable melanoma. The direct injection of treatments into melanoma lesions can cause cell lysis and induce a local immune response, and might be associated with a systemic immune response. Directly injecting immunotherapies into tumours achieves a high local concentration of immunostimulatory agent while minimising systemic exposure and, as such, HIT-IT agents are associated with lower toxicity than sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 99 publications
(149 reference statements)
0
26
0
Order By: Relevance
“…T-VEC is an engineered virus, that only replicates in tumor cells and induces secretion of the cytokine GM-CSF from its transgene. Oncolytic viruses can induce local and systemic anti-tumor immune responses through immunogenic cell death induction ( 75 ). The local release of GM-CSF results in recruitment and activation of DCs, but likely will also drains to nearby TDLN to activate lymph node resident (LNR)-DCs and promote T cell priming and activation.…”
Section: In Conclusion: the Rise Of Local Immunotherapymentioning
confidence: 99%
“…T-VEC is an engineered virus, that only replicates in tumor cells and induces secretion of the cytokine GM-CSF from its transgene. Oncolytic viruses can induce local and systemic anti-tumor immune responses through immunogenic cell death induction ( 75 ). The local release of GM-CSF results in recruitment and activation of DCs, but likely will also drains to nearby TDLN to activate lymph node resident (LNR)-DCs and promote T cell priming and activation.…”
Section: In Conclusion: the Rise Of Local Immunotherapymentioning
confidence: 99%
“…Even though the anti-tumor efficacy of intratumoral IL-2 appears to be durable, it is limited to the injected lesions suggesting that intratumoral IL-2 does not have strong systemic effects. Unlike systemic IL-2, however, intratumoral IL-2 is generally well tolerated [ 79 , 80 ]. In a phase 2 study, tavokinogene telseplasmid—a synthetic plasmid encoding the cytokine IL-12—demonstrated the induction of an anti-tumor immune response and a high control rate in patients with CM.…”
Section: Intratumoral Tumor Therapy and Combinationsmentioning
confidence: 99%
“…Moreover, it has been detected that cyclic dinucleotides may represent immune adjuvants by activating STING, in turn stimulating a pro-inflammatory immune response. Hence, phase 1 studies on 2 intratumoral STING agonists have been initiated [ 79 , 83 ]. A synergy between intratumoral agents and ICI may be expected.…”
Section: Intratumoral Tumor Therapy and Combinationsmentioning
confidence: 99%
See 2 more Smart Citations